Lurking in the Shadows: The Impact of Emissions Target Setting on Carbon Pricing and Environmental Efficiency - Barry Quinn; Ronan Gallagher; Timo Kuosmanen (Queen's University Belfast, Queen's Management School, 2021)
This paper examines the impact of Kyoto Protocol target setting regime on environmental efficiency and carbon shadow pricing. We extract shadow price estimates and efficiency scores from a comprehensive dataset of 125 countries in the first Kyoto commitment period (2008-2012) using a stochastic non-parametric estimation framework. We estimate CO2 marginal abatement costs which: are significantly higher for target setting countries; increase over the sample period, and are an order of magnitude greater than the prevailing emissions pricing mechanisms. Our findings provide insights into the consequences of policies to curb unwanted by-products in a regulated system and shed light on the price efficiency of carbon markets
Keywords: 330